O Estado, o mercado e o tributo: como o modelo de tributa????o ?? capaz de alterar a hist??ria do Brasil - Moraes, Andr?? Souza Pedroso de (2017)
The present paper aims to analyze how does institutions ??? State, Economy and Tax ??? works in Brazilian society. Actually, this research will follow some steps based on many theories in pursuit of an answer for the question: the Brazilian tax model helps society to turn into reality the constitutional values and political ideology? If not, how can a tax model change the Brazilian future? To answer that we will use Luhmann???s theory about social systems as a magnifying glass over Brazilian social and institutional history. After that we`ll confront real database with constitutional text and verify what is Brazilian`s constitutional ideology and if or how tax model works with it.